Serological and molecular detection of Borrelia burgdorferi sensu lato and Anaplasmataceae in rodents - Štefančíková, Astéria; Derdáková, Markéta; Lenčáková, Daniela; Ivanová, Renáta; Stanko, Michal; Čisláková, Lýdia; Peťko, Branislav (Folia microbiologica, 2008)
The presence of Anaplasma spp. and Borrelia burgdorferi sensu lato in rodents from Eastern Slovakia were followed by serological and molecular methods. The seroprevalence for Borrelia was detected in 16.6 %, for Anaplasmataceae (APT) in 13.2 % and co-occurrence of Borrelia and APT in 7.5 %. Out of 110 ear biopsies of rodents, 5 were B. afzelii-positive. Five biopsies tested positive with the Ehr521-Ehr747 primers amplifying all the members of the family APT. A. phagocytophilum was detected in 1.8 %, 2.7 % were infected with Anaplasma-like organisms. Co-occurrence of Borrelia and Anaplasma in ear biopsies was found in 1.8 %. The circulation of both Borrelia and Anaplasma in the region of Eastern Slovakia was confirmed.
Keywords: protilátky bakteriální; lymeská nemoc; Animals; Enzyme-Linked Immunosorbent Assay; Anaplasmataceae Infections; nemoci hlodavců; polymerázová řetězová reakce; Disease Reservoirs; polymorfismus délky restrikčních fragmentů; Polymerase Chain Reaction; zdroje nemoci; Rodent Diseases; DNA bakterií; Reproducibility of Results; DNA, Bacterial; Slovakia; Molecular Sequence Data; Borrelia burgdorferi komplex; zevní ucho; Mice; Murinae; Arvicolinae; myši; Antibodies, Bacterial; Borrelia burgdorferi Group; Polymorphism, Restriction Fragment Length; reprodukovatelnost výsledků; molekulární sekvence - údaje; ELISA; séroepidemiologické studie; Anaplasmataceae; Seroepidemiologic Studies; Lyme Disease; Sequence Alignment; infekce bakteriemi čeledi Anaplasmataceae; Slovenská republika; zvířata; Ear, External; sekvenční seřazení